2011
DOI: 10.1213/ane.0b013e31820d9787
|View full text |Cite
|
Sign up to set email alerts
|

Local Anesthetic Blockade of Peripheral Nerves for Treatment of Neuralgias

Abstract: Because all reviewed articles were only single case reports or case series, no reliable conclusion could be drawn concerning the effectiveness of nerve blocks with local anesthetics in neuralgia. However, 2 features of the analyzed reports-the large magnitude of the effect and the high consistency of the reported outcome-indicate that future research efforts are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(35 citation statements)
references
References 47 publications
1
33
0
1
Order By: Relevance
“…Not all observations can be accounted for by this mechanism. There are three phenomena associated with responses to nerve blocks described in the literature: pain relief may outlast the conduction blockade; block distal to the site of the pain inducing lesion may stop or alleviate the pain and blocking a peripheral nerve supplying a large part, but not the whole of the region of pain, may provide pain relief in the entire region [10,11].…”
Section: Discussionmentioning
confidence: 99%
“…Not all observations can be accounted for by this mechanism. There are three phenomena associated with responses to nerve blocks described in the literature: pain relief may outlast the conduction blockade; block distal to the site of the pain inducing lesion may stop or alleviate the pain and blocking a peripheral nerve supplying a large part, but not the whole of the region of pain, may provide pain relief in the entire region [10,11].…”
Section: Discussionmentioning
confidence: 99%
“…On a first glance, it seems irrational to expect a therapeutic effect by the injection of a local anesthetic, as the effect on nerve conduction is short lasting. However, a systematic review found consistent evidence for an effect of local anesthetic injections that exceeds the duration of the conduction blockade [26]. No study included in the review had negative results, but all reviewed articles were single case reports or case series, preventing reliable conclusions.…”
Section: Therapeutic Blocksmentioning
confidence: 99%
“…Reports have suggested that anesthetic blocks as well as systemic administration of lidocaine may produce longlasting effects outlasting the conduction blockade and that blocks distally to the site of the nerve lesion may produce complete pain DOI relief [5,6], but the underlying mechanisms are unknown and properly controlled studies are lacking [4]. In the study by Miclescu et al some patients had an effect that lasted more than 24 h, but most patients had temporary, short-lasting effects [2].…”
Section: Local Anesthetics and The Mechanisms Of Neuropathic Painmentioning
confidence: 99%